ORIENTASI TAFSIR, KOLONIALISME, DAN KEBANGSAAN (STUDI KONSTRUKSI TAFSIR VERBAL TUAN GURU ZAINUDDIN TERHADAP QS. AL-MAIDAH 44-45 DI UNIVERSITAS PTIQ JAKARTA - Darwis Hude; Zulkarnaen Zulkarnaen; Lukman Hakim; Ahmad Thib Raya; Imam Mutaqien; Irpan Husaini (MADANI Abdimas : Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
This study aims to analyze the verbal exegesis of Tuan Guru Zainuddin Abdul Madjid (1908-1997) on QS. Al-Maidah/5: 44-45. Tuan Guru was a traditional Islamic scholar born out of the Madrasah Shaulatiyyah in Mecca. This research is important for two reasons: first, it provides insights into how the Quran, exegesis, and the context during the colonial period are intertwined; second, it explains how exegesis serves as a historical document of the Lombok community where Tuan Guru lived. The hypothesis is that Tuan Guru’s verbal exegesis is a contextual interpretation emerging from the context of the struggle to maintain Indonesia's independence in 1946. Consequently, he refers to the term "colonizers" in his interpretation of QS. Al-Maidah/5: 44-45. The theoretical framework used in this study is Karl Mannheim's Sociology of Knowledge theory. This theory assumes that understanding anything is impossible without understanding its social constructs. The primary source for this research is an interview with one of Tuan Guru’s students, documented in a book. The secondary sources include books and journal articles that discuss Tuan Guru’s history. The research will be conducted by: first, collecting the necessary primary data; second, analyzing this data; third, presenting the findings in a logical and systematic manner. These three processes aim to clarify the results or conclusions of this study. The findings reveal that Tuan Guru’s interpretation encompasses four social constructs: first, the context of the attack on the NICA military post; second, awareness of religious authority; third, a strong connection with Madrasah Shaulatiyyah; fourth, Tuan Guru’s experiences before traveling to Mecca